Perbedaan NPF dan FDR Bank Muamalat antara Sebelum dan Selama Pandemi Covid-19 - Dematria Pringgabayu; Kurnia Fajar Afgani; Alda Ricederia (Masoem University, 2021)
This research was conducted to analyze and describe the NPF and FDR ratio of Bank Muamalat Indonesia between before and during the Covid-19 pandemic. The method used in this research is quantitative with research data in the form of secondary data. The data were collected using the documentation method and analyzed using the descriptive statistic and independent sample t-test. The results of the study state that the NPF and FDR value of Bank Muamalat Indonesia was differ between before and during the Covid-19 pandemic, although not statistically significant. The difference in terms of NPF indicates that the financing risk faced by Bank Muamalat Indonesia during the pandemic period is greater. The difference in terms of FDR indicates the existence of prudence from banks in distributing financing to the public because the business situation is not conducive during the Covid-19 pandemic.